Application of the knowledge-based approach to strain selection for a bioaugmentation process of phenanthrene- and Cr(VI)-contaminated soil - Ibarrolaza, Agustin (2011)
Aims: The objective of this study was to apply the knowledge-based approach to the selection of an inoculum to be used in bioaugmentation processes to facilitate phenanthrene degradation in phenanthrene- and Cr(VI)-co-contaminated soils. Methods and Results: The bacterial community composition of phenanthrene and phenanthrene- and Cr(VI)-co-contaminated microcosms, determined by denaturing gradient gel electrophoresis analysis, showed that members of the Sphingomonadaceae family were the predominant micro-organisms. However, the Cr(VI) contamination produced a selective change of predominant Sphingomonas species, and in co-contaminated soil microcosms, a population closely related to Sphingomonas paucimobilis was naturally selected. The bioaugmentation process was carried out using the phenanthrene-degrading strain S. paucimobilis 20006FA, isolated and characterized in our laboratory. Although the strain showed a low Cr(VI) resistance (0·250mmoll-1); in liquid culture, it was capable of reducing chromate and degrading phenanthrene simultaneously. Conclusion: The inoculation of this strain managed to moderate the effect of the presence of Cr(VI), increasing the biological activity and phenanthrene degradation rate in co-contaminated microcosm. Significance and Impact of the Study: In this study, we have applied a novel approach to the selection of the adequate inoculum to enhance the phenanthrene degradation in phenanthrene- and Cr(VI)-co-contaminated soils. © 2011 The Authors. Journal of Applied Microbiology